Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To find the minimum value of the expression [tex]\( a \sqrt{b^2 + 1} + b \sqrt{c^2 + 1} + c \sqrt{a^2 + 1} \)[/tex] given that [tex]\( a, b, c \in \mathbb{R}^+ \)[/tex] and [tex]\( a b + a c + b c = 1 \)[/tex], follow these steps:
1. Understand the constraint: [tex]\( a b + a c + b c = 1 \)[/tex].
2. Make an initial guess: Because the expressions involve symmetric summations and products, one might guess that the solution could involve [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] being equal. This suggests trying [tex]\(a = b = c\)[/tex].
3. Substitute [tex]\(a = b = c\)[/tex] into the constraint:
[tex]\[ a^2 + a^2 + a^2 = 1 \implies 3a^2 = 1 \implies a^2 = \frac{1}{3} \implies a = \sqrt{\frac{1}{3}} = \frac{1}{\sqrt{3}} \][/tex]
Thus, we set [tex]\( a = b = c = \frac{1}{\sqrt{3}} \)[/tex].
4. Evaluate the objective function:
[tex]\[ f(a, b, c) = a \sqrt{b^2 + 1} + b \sqrt{c^2 + 1} + c \sqrt{a^2 + 1} \][/tex]
Substituting [tex]\( a = b = c = \frac{1}{\sqrt{3}} \)[/tex]:
[tex]\[ f\left(\frac{1}{\sqrt{3}}, \frac{1}{\sqrt{3}}, \frac{1}{\sqrt{3}}\right) = \left(\frac{1}{\sqrt{3}}\right) \sqrt{\left(\frac{1}{\sqrt{3}}\right)^2 + 1} + \left(\frac{1}{\sqrt{3}}\right) \sqrt{\left(\frac{1}{\sqrt{3}}\right)^2 + 1} + \left(\frac{1}{\sqrt{3}}\right) \sqrt{\left(\frac{1}{\sqrt{3}}\right)^2 + 1} \][/tex]
5. Simplify the expressions inside the square roots:
[tex]\[ \left(\frac{1}{\sqrt{3}}\right)^2 + 1 = \frac{1}{3} + 1 = \frac{4}{3} \][/tex]
Therefore,
[tex]\[ \sqrt{\frac{4}{3}} = \frac{2}{\sqrt{3}} = \frac{2 \sqrt{3}}{3} \][/tex]
6. Evaluate the simplified expression:
[tex]\[ f\left(\frac{1}{\sqrt{3}}, \frac{1}{\sqrt{3}}, \frac{1}{\sqrt{3}}\right) = 3 \cdot \left(\frac{1}{\sqrt{3}}\right) \cdot \frac{2 \sqrt{3}}{3} \][/tex]
Simplifying further:
[tex]\[ 3 \cdot \frac{1}{\sqrt{3}} \cdot \frac{2 \sqrt{3}}{3} = 3 \cdot \frac{2}{3} = 2 \][/tex]
Thus, the minimum value of the expression [tex]\( a \sqrt{b^2 + 1} + b \sqrt{c^2 + 1} + c \sqrt{a^2 + 1} \)[/tex] given [tex]\( ab + ac + bc = 1 \)[/tex] and [tex]\( a, b, c \in \mathbb{R}^+ \)[/tex] is [tex]\(\boxed{2}\)[/tex].
1. Understand the constraint: [tex]\( a b + a c + b c = 1 \)[/tex].
2. Make an initial guess: Because the expressions involve symmetric summations and products, one might guess that the solution could involve [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] being equal. This suggests trying [tex]\(a = b = c\)[/tex].
3. Substitute [tex]\(a = b = c\)[/tex] into the constraint:
[tex]\[ a^2 + a^2 + a^2 = 1 \implies 3a^2 = 1 \implies a^2 = \frac{1}{3} \implies a = \sqrt{\frac{1}{3}} = \frac{1}{\sqrt{3}} \][/tex]
Thus, we set [tex]\( a = b = c = \frac{1}{\sqrt{3}} \)[/tex].
4. Evaluate the objective function:
[tex]\[ f(a, b, c) = a \sqrt{b^2 + 1} + b \sqrt{c^2 + 1} + c \sqrt{a^2 + 1} \][/tex]
Substituting [tex]\( a = b = c = \frac{1}{\sqrt{3}} \)[/tex]:
[tex]\[ f\left(\frac{1}{\sqrt{3}}, \frac{1}{\sqrt{3}}, \frac{1}{\sqrt{3}}\right) = \left(\frac{1}{\sqrt{3}}\right) \sqrt{\left(\frac{1}{\sqrt{3}}\right)^2 + 1} + \left(\frac{1}{\sqrt{3}}\right) \sqrt{\left(\frac{1}{\sqrt{3}}\right)^2 + 1} + \left(\frac{1}{\sqrt{3}}\right) \sqrt{\left(\frac{1}{\sqrt{3}}\right)^2 + 1} \][/tex]
5. Simplify the expressions inside the square roots:
[tex]\[ \left(\frac{1}{\sqrt{3}}\right)^2 + 1 = \frac{1}{3} + 1 = \frac{4}{3} \][/tex]
Therefore,
[tex]\[ \sqrt{\frac{4}{3}} = \frac{2}{\sqrt{3}} = \frac{2 \sqrt{3}}{3} \][/tex]
6. Evaluate the simplified expression:
[tex]\[ f\left(\frac{1}{\sqrt{3}}, \frac{1}{\sqrt{3}}, \frac{1}{\sqrt{3}}\right) = 3 \cdot \left(\frac{1}{\sqrt{3}}\right) \cdot \frac{2 \sqrt{3}}{3} \][/tex]
Simplifying further:
[tex]\[ 3 \cdot \frac{1}{\sqrt{3}} \cdot \frac{2 \sqrt{3}}{3} = 3 \cdot \frac{2}{3} = 2 \][/tex]
Thus, the minimum value of the expression [tex]\( a \sqrt{b^2 + 1} + b \sqrt{c^2 + 1} + c \sqrt{a^2 + 1} \)[/tex] given [tex]\( ab + ac + bc = 1 \)[/tex] and [tex]\( a, b, c \in \mathbb{R}^+ \)[/tex] is [tex]\(\boxed{2}\)[/tex].
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.